2022
DOI: 10.47391/jpma.13896
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of depression among undergraduate medical students of a private medical college in Lahore

Abstract: Objective: To assess the prevalence and determinants of depression in undergraduate medical students within their learning environment. Methods: The descriptive cross-sectional study was conducted at the Lahore Medical and Dental College, Lahore, Pakistan, from May to June 2015, and comprised medical students of all the five professional years. A structured questionnaire was used to collect data. Section one of the questionnaire related to demographic information, section two comprised Patient health que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…We found that attending a private university increases the prevalence of depression and anxiety. Previous studies reported similar results [35,36]; however, in Bangladesh [37] and Nigeria [38], it was found that students from public universities had higher estimates. The association between studying at a private university and depression and anxiety could be explained by the pressure on students to repay high payments from their parents or funders by obtaining high grades.…”
Section: Factors Associated With Mental Health Disorderssupporting
confidence: 62%
“…We found that attending a private university increases the prevalence of depression and anxiety. Previous studies reported similar results [35,36]; however, in Bangladesh [37] and Nigeria [38], it was found that students from public universities had higher estimates. The association between studying at a private university and depression and anxiety could be explained by the pressure on students to repay high payments from their parents or funders by obtaining high grades.…”
Section: Factors Associated With Mental Health Disorderssupporting
confidence: 62%